Konsep Restorative Justive Dalam Hukum Acara Terhadap Pembelaan Terpaksa - Faturohman Faturohman; Ratu Nabilah Afifah; Abdul Muid; Desi Pratiwi (QAIMUDDIN: Journal of Constitutional Law Review, 2021)
This journal aims to analyze criminal acts using the conventional justice system and examine opportunities for restorative justice to be applied as an innovation in resolving criminal cases in Indonesia. The problem discussed is the mechanism for expanding the application of the concept of restorative justice in the criminal justice system in forced defense. The research method used is normative legal research. The conclusion drawing technique used uses a deductive method. Based on the research results, given the differences and inequalities in the application of the concept of restorative justice in the Police, Prosecutor's Office and Supreme Court which regulate procedural law regarding the implementation or implementation of the concept of restorative justice in resolving criminal cases committed by adults, the Government and DPR are expected to immediately formulate policies - policies regarding the concept of restorative justice issued by the criminal justice sub-system into a Legislative Regulation, either in the form of a law or formulated in the Draft Criminal Procedure Code (RKUHAP) and the Draft Criminal Code (RKUHP).